Information services in counseling and locus of control toward communication between parents and children’s - Evi Fitriyanti; Sabrina Dachmiati; Hengki Satrianta (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
The aim of this research is to know how much contribution given by informationservices in counseling and locus of control toward communication between parents and children. This research is a quantitative research using survey. This research was conducted in Komunitas Bunda Condet. The sample for this study came to 44 people taken by saturated sample distribution technique. Data were collected through a questionnaire. Data was analyzed by using multiple regression test with the help of SPSS 22 for windows. The results showed that information services and locus of control contribute to communication between parents and children. These results prove that communication quality can be improved by taking into account information services and locus of control.